2017
DOI: 10.1155/2017/6710931
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Sessile Serrated Adenomas Are More Prevalent in Caucasians, and Gastroenterologists Are Better Than Nongastroenterologists at Their Detection

Abstract: Background and Aim Proximal sessile serrated adenomas (PSSA) leading to colorectal cancer (CRC) represent an alternate pathway for CRC development. In this study, we aim to determine the prevalence of PSSAs and the impact of patient, colonoscopy, and endoscopist-related factors on PSSA detection. Methods Patients ≥ 50 years of age undergoing a screening colonoscopy between 2012 and 2014 were included. Detection rates based on patient gender, race, colonoscopy timing, fellow participation, bowel preparation qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…45,62,73 Reviews of recently published colonoscopy series studies found that an average 2%-8% of SSLs are detected (akin to prevalence) in average-risk patients undergoing colonoscopy. 8,54,58,62,[73][74][75][76][77][78][79][80][81][82] Among high-detecting endoscopists and centers, however, the reported prevalence values are 13%-20% ( Figure 3A, Supplementary Table 2). 45,54,62,74,78 It is a reasonable assumption that detection of SSLs among high detectors is the best estimate of the true prevalence of these lesions.…”
Section: Prevalence Based On Endoscopic Datamentioning
confidence: 99%
See 1 more Smart Citation
“…45,62,73 Reviews of recently published colonoscopy series studies found that an average 2%-8% of SSLs are detected (akin to prevalence) in average-risk patients undergoing colonoscopy. 8,54,58,62,[73][74][75][76][77][78][79][80][81][82] Among high-detecting endoscopists and centers, however, the reported prevalence values are 13%-20% ( Figure 3A, Supplementary Table 2). 45,54,62,74,78 It is a reasonable assumption that detection of SSLs among high detectors is the best estimate of the true prevalence of these lesions.…”
Section: Prevalence Based On Endoscopic Datamentioning
confidence: 99%
“…69,71 White race is a consistent risk factor for SSLs in US and European studies of average-risk patients, whereas black, Asian, and American Indian/Alaskan Native populations have a lower prevalence. 80,99,100,102,103 In a large US study with data from 1.6 million screening colonoscopies, white men and women were found to have a 2-to 3-fold increase in risk of SSLs compared to black or Asian individuals (Supplementary Figure 1B). 99 Patients with a family history of CRC or a personal history of premalignant serrated polyps also have an increased risk of SSLs.…”
Section: Nonmodifiable Risk Factorsmentioning
confidence: 99%
“…2,3 However, the racial disparity between African Americans and white Americans in CRC mortality, and prevalence of adenomas and polyps (which are the precursors to CRC) have persisted. 4–7 In addition to race, physician-related factors (e.g., medical specialty) and insurance coverage have also been associated with CRC screening and disease outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 GEs are more likely than other specialties to remove adenomas and polyps during a colonoscopy. 4,11 Research has also shown that having a GE perform the screening colonoscopy is associated with a lower rate of CRC after a negative colonoscopy. 12,13 Furthermore, CRC patients experience better postoperative outcomes and overall survival when surgery was performed by a CRS than when surgery was performed by a general surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…In an evaluation of endoscopist characteristics and their effects on PSPDR, Sarvepalli et al [4] found in multivariate analysis, adjusting for patient and procedural factors, that the only significant factors affecting PSPDR were the length of time since completing training and annual colonoscopy volume-physician specialty-also had no significant effect. In contrast, Parikh et al [7] demonstrated that in the adjusted analysis, gastroenterologists had significantly higher PSPDR compared to non-gastroenterologists for screening colonoscopies. Importantly, prior studies compare cohorts of endoscopists that are more mixed-often combining general surgeons and colorectal surgeons, or all non-gastroenterologists into a single group.…”
mentioning
confidence: 86%